Bank efficiency and practice of earnings management: a study on listed commercial banks of Bangladesh - Naznin Sultana Chaity; K.M. Zahidul Islam (Emerald Publishing Limited, 2021)
The purpose of the study is to determine the relationship between bank efficiency in terms of corporate governance guidelines and the extent of practice of earnings management (EM).Archival data of listed private commercial banks of Dhaka Stock Exchange over the period of 2007–2016 relating to corporate governance and earnings management are collected and analyzed using parametric and non-parametric methods (efficiency analysis) and applying panel regression analysis.The same distribution pattern and have low degree of the correlation (0.248) among them. It is found that private commercial banks of Bangladesh, on average, display efficiency level of 80.84%. The average value of discretionary loan loss provision (i.e. measure of earnings management) is 0.4249 and this indicates the presence of earnings management. The relation between earnings management and efficiency score in both cases of two-step system generalized methods of moments (GMMs) and difference GMM are found to be negative. The negative coefficients (−0.7969 and −0.57) indicate that as the efficiency increases, the practice of earnings management by the private commercial bank reduces. By estimating efficiency based on corporate governance guidelines and detecting the existence of EM, the major contribution of the study is establishing the relationship between bank efficiency based on compliance with corporate governance guidelines and managerial practice of earnings management in Bangladesh. Empirical results of the study have also established the fact that the more efficient the management of the banks are, the less likely it will practice earnings management under the compliance of corporate governance guidelines in Bangladesh.This research study has some limitations. Only conventional banks are considered for the study, with the exception of Islamic banks. Comparison between conventional banks and Islamic banks could have been done.Based on the literature study, the effectiveness of corporate governance aligns with decreasing agency conflict, protection of shareholders' interests and restrain management from self-serving activities (i.e. practice of earnings management). The empirical results of the study established these facts. Regulators should give more emphasis on effective implementation of good governance.To the best of the authors' knowledge, this may be the first to empirically determine the relationship between efficiency estimation based on corporate governance and earnings management in case of listed commercial banks of Bangladesh.